Intramontane Ebenen im Hochland von Godjam (Äthiopien) - Semmel, Arno (ERDKUNDE, 1963)
The paper describes and genetically interprets level surfaces of the highland of Godjam (Ethopia). They are similar to the south-east Asian intra-mountain plateaux (intramontanen Ebenen) as described by W. Credner. They differ from Rumpfflächen proper by being surrounded on all sides by mountain ridges. Intra-mountain plateaux are not as a rule tectonic depressions but genuine erosion features. Proof of this is mainly as follows: 1. Within the plateaux fresh basalt forming the solid geology comes tho the surface in many places; 2. Within and on the margins of the plateaux accumulations of unweathered blocks of basalt are found and can only be explained as remains of basalt sheets weathered in situ and subsequently eroded. A fluviatile or solifluctive transport of these blocks can be discounted. The erosion within the plateaux takes place by wash troughs and wash gulleys (Spülmulden and Spülrinnen). These join the rivers which cross the plateaux. The rivers lower the local base level by linear corrosion and thus create the prerequisites for the erosion of the plateaux themselves. The original formation of the plateaux is due to the consequences of selective weathering. Deeply weathered rocks are removed more quickly than those weathered little or not at all. Once a depression has come into being it is enlarged horizontally and is also deepened by the processes of sheet wash. These processes have been continuing more or less unchanged since the lava flows ceased.